Fabry–Perot Cavity Sensing Probe with High Thermal Stability for an Acoustic Sensor by Structure Compensation - Jin Cheng; Yu Zhou; Xiaoping Zou (Sensors, 2018)
Fiber Fabry–Perot cavity sensing probes with high thermal stability for dynamic signal detection which are based on a new method of structure compensation by a proposed thermal expansion model, are presented here. The model reveals that the change of static cavity length with temperature only depends on the thermal expansion coefficient of the materials and the structure parameters. So, fiber Fabry–Perot cavity sensing probes with inherent temperature insensitivity can be obtained by structure compensation. To verify the method, detailed experiments were carried out. The experimental results reveal that the static cavity length of the fiber Fabry–Perot cavity sensing probe with structure compensation hardly changes in the temperature range of −20 to 60 °C and that the method is highly reproducible. Such a method provides a simple approach that allows the as-fabricated fiber Fabry–Perot cavity acoustic sensor to be used for practical applications, exhibiting the great advantages of its simple architecture and high reliability.